Effects of Solid-Liquid Ratio, Time, and Temperature on Water Extraction of Anthocyanin from Campbell Early Grape - Ryu, Dayeon; Park, Hyun-Mee; Koh, Eunmi (SPRINGER, 2020)
This study was conducted to optimize anthocyanin extraction conditions from Campbell Early grape using acidified water. A response surface methodology with Box-Behnken design consisting of 17 experiments was employed to investigate the effects of three variables. The grape was extracted at three different solid-liquid ratios (1/30-1/50 g/mL), extraction times (10-60 min), and extraction temperature (30-80 degrees C). Under optimum conditions (1/50 g/mL, 10 min, and 80 degrees C), experimental values were 197.52 mg/100 g for total anthocyanins, 1363.12 mg/100 g for total phenols, and 315.79 mg/100 g for 2,2 '-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) radical scavenging activity in the dry weight basis. The difference between experimental and predicted values was less than 5.1%, indicating that the model fits well. Eight anthocyanins were identified in the extract of Campbell Early grape using an ultra-performance liquid chromatograph (UPLC) with a tandem mass spectrometry. Three major anthocyanins were cyanidin-3-(coumaroyl)-5-diglucoside (44.1% of the total), delphinidin-3-(coumaroyl)-5-diglucoside (20.7% of the total), and peonidin-3-(coumaroyl)-5-diglucoside (12.4% of the total).
Keywords: ANTIOXIDANT ACTIVITY; PHENOLIC-COMPOUNDS; ASSISTED EXTRACTION; NATURAL COLORANTS; OPTIMIZATION; IDENTIFICATION; ULTRASOUND; FRUITS; WINES; L.